The effects of ergogenic aid supplementation on the sprint capacity of male cyclists - Hansen, C. A. (1999)
The purpose of this investigation was to evaluate the effects of ergogenic aid supplementation, specifically different formulated sports drinks with reference to magnesium, on the sprint capacity (mean anaerobic power, peak anaerobic power, lowest anaerobic power, rate of fatigue, and blood lactate concentrations) in male cyclists. The investigation followed a double-blind format with participants randomly assigned into treatment groups. All participants completed a three-day diet analysis during each supplementation period. At the end of each supplementation period participants performed a 40-km bicycle ride on a stationary trainer at 80% of their maximum heart rate followed by a Wingate Anaerobic Power Test at 0.075 kp/kg. Three minutes post Wingate, an Accusport portable blood lactate analyzer measured blood lactate concentrations. A repeated measures ANOVA revealed significant differences in mean anaerobic power (F=5.680, p=0.035) between ergogenic aid A (392 mg of magnesium per day) and ergogenic aid B (60.6 mg of agnesium per day). However, significance was not reached in peak anaerobic power (F=2.737, p=0.124), lowest anaerobic power (F=2.083, 0.175), rate of fatigue (F=0.071, p=0.794), and blood lactate concentrations (F=0.282, p=0.607). Dependent t-tests revealed no significant differences between ergogenic aid A and B when added to the participants diet: potassium (p=0.072), calcium (p=0.503), carbohydrates (p=0.270), and total kilocalories (p=.064). In contrast, there was a significant difference in magnesium (p<0.001) between ergogenic aid A and B. In conclusion, supplementation of magnesium (392 mg per day) may be beneficial in the enhancement of anaerobic performance in competitive male cyclists.